Public Knowledge of Diabetes and Hypertension in Metropolitan Cities, Indonesia - I Gede Mahatma Yuda Bakti; Sumardjo Sumardjo; Anna Fatchiya; Agus Fanar Syukri (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2021)
Non-communicable diseases (NCDs), such as diabetes and hypertension, contributed significantly to the mortality rate in Indonesia. Citizens’ unhealthy behaviors have led to an increased risk of diabetes and hypertension. This study aimed to investigate the level of public knowledge regarding diabetes and hypertension. Data were collected through a survey using questionnaires. There were 307 respondents from Medan (n=190) and Jakarta (n=118). The sample was dominated by the female (68,5%) and high school graduates (76.3%). The data revealed that 2.3 percent of the respondents suffered or are currently suffering from diabetes and 3.6 percent of the respondents suffered or are currently suffering from hypertension. The results showed that the level of public knowledge regarding diabetes (65.91%) and hypertension (58.15%) was not ideal in general. Many citizens still did not understand various aspects of diabetes and hypertension, such as the causes, consequences, treatments, and characteristics of their sufferer. This study also found that there are group differences in the level of public knowledge based on gender and geographical location.